PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING(CTL) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 017 BAGAN PUNAKMERANTI KECAMATAN BANGKOKABUPATEN ROKAN HILIR - Susilawati '; Damanhuri Daud Damanhuri Daud; Syahrilfuddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : Educationclassactionoriginatedfromthe lowstudent learning outcomes, problems ineducationcan beformulatedas follows: Isthe application ofContextual TeachingAndLearningapproachcanimprovescience learningoutcomesElementary Schoolfourth grade students017ChartPunakMerantiRokan HilirDistrict ofBangko?. The purposeof thisresearchistoimprovescience learningoutcomesElementary Schoolfourth grade students017ChartPunakMerantiBangkoRokanHilirsubdistrict. Studentsof the 27peopleconsistingof16male studentsand11female students.The actionisanalyzedthe implementation ofContextual TeachingAndLearningapproachandoutcomevariablesproblemthatstudentslearn science, the dataobtained throughteacherobservation sheetactivitiesand their effects onstudent learning outcomesafter followingthelearning model. Based on the researchthat has beendone showsan increase instudents'sciencelearning achievementofstudentlearning outcomesobtainedusing theimplementation ofContextual TeachingAndLearningapproach, carried outtwocycles, thescoresbasicvalue - average67.22studentsafterexecutingthe first cycleof learning outcomesstudentsachievevalue - average69.25isincreased by3%. Thenaverage-69.25averagefirst cycleandincreasedin the second cyclewithvalue - average76.48isincreased by10%. Increasedvalue - averagethisit can be concludedthat theapplication of theuse ofContextual TeachingAndLearningapproachcanincreasestudentlearning outcomesIPAChart017fourth gradeMerantiPunakBangkoRokanHilirsubdistrict.   Key Word: Contextal Teaching and Learning, IPA Learning Outcomes